Treatment Modifications in Acute Coronary Syndrome Patients Treated with Ticagrelor: Insights from the FORCE-ACS Registry - van der Sangen, Niels M.R.; Azzahhafi, Jaouad; Chan Pin Yin, Dean R.P.P.; Zaaijer, Lucas J.G.; van den Broek, Wout W.A.; Walhout, Ronald J.; Tjon Joe Gin, Melvyn; Pisters, Ron; Nicastia, Deborah M.; Langerveld, Jorina; Vlachojannis, Georgios J.; van Bommel, Rutger J.; Appelman, Yolande; Henriques, José P.S.; Kikkert, Wouter J.; ten Berg, Jurriën M. (Thrombosis and Haemostasis, 2024)
Patients presenting with acute coronary syndrome (ACS) are frequently treated with the P2Y12-inhibitor ticagrelor. Some patients prematurely discontinue ticagrelor, but the incidence of reasons for and clinical implications of treatment modification are relatively unknown.Data from 4,278 ACS patients (mean age: 63.6 years, 26.1% women) who were discharged on ticagrelor and enrolled in the FORCE-ACS registry between 2015 and 2020 were used. Treatment modifications were categorized as physician-recommended discontinuation, alteration, interruption, or disruption and occurred in 26.7, 20.1, 2.8, and 3.1% of patients within 12 months of follow-up (Visual Summary). Underlying reasons for treatment modification differed per type of modification. Overall, the rate of ischemic events defined as all-cause death, myocardial infarction, or stroke was 6.6% at 12 months of follow-up. Cox regression analysis using time-updated modification variables as independent variables showed that treatment interruption (adjusted hazard ratio [HR]: 2.93, 95% confidence interval [CI]: 1.48–5.79, p < 0.01) and disruption (adjusted HR: 2.33, 95% CI: 1.07–5.07, p = 0.03) were associated with an increased risk of ischemic events even after adjustment for relevant confounders. Discontinuation and alteration were not associated with increased ischemic risk.In clinical practice, treatment modifications in ACS patients discharged on ticagrelor are common, although type and reasons for modification are heterogeneous. Treatment interruption and disruption are associated with excess cardiovascular risk.
Keywords: acute coronary syndrome; treatment modifications; ticagrelor